Searching for an Anthropo(s)cene in the Uplands of Mid Wales. Issue 2 (3rd July 2017) - Griffiths, Hywel M.; Goodwin, Gavin; Keevil, Tyler; Salisbury, Eurig; Tooth, Stephen; Roberts, Dewi
Abstract : This essay presents the responses of four creative writers to the highly modified landscapes of the Cambrian Mountains in mid Wales. Through a tour of the historic mine site of Cwmystwyth and the dams of Cwm Elan, our aims were to engage with the concept of the Anthropocene in a landscape that could be emblematic of the proposed new geological interval. Through poems and prose inspired by these landscapes, the physical, social, cultural, and political processes shaping them are explored. The pieces have a strong sense of place, and touch on themes of pollution of the environment by heavy metals, geomorphological impacts of dams, and the human stories associated with those places. We demonstrate the great potential of such places and landscapes as sites where artistic creativity and science can engage and collaborate to find ways of communicating concepts such as the Anthropocene and the anthroposcenic.